2008
DOI: 10.1055/s-0028-1098959
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Management of Infected Mandibular Fractures

Abstract: The treatment of infected mandibular fractures has advanced rather dramatically over the past 50 years. Immobilization with maxillomandibular fixation and/or splints, removal of diseased teeth in the fracture line, external fixation, use of antibiotics, debridement, and rigid internal fixation has played a role in management. Perhaps the most important advance was the realization that infected fractures also result from moving fragments and nonvital bone, not just bacteria. Controlling movement and eliminating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 10 publications
(14 reference statements)
1
13
0
Order By: Relevance
“…In addition, these data suggest that the choice for an open procedure was not based on the patient's dental health alone. External fixation, which was used in 2.9% of cases, is reserved for the most complicated fractures with large soft-tissue defects or when immediate jaw bone repair is not possible 13. These surgical details and the distribution of procedures in this study indicate that our patient sample was in fact suffering from more complex fracture patterns, given that conservative treatment was so infrequently applied (Table 2).…”
Section: Discussionmentioning
confidence: 89%
“…In addition, these data suggest that the choice for an open procedure was not based on the patient's dental health alone. External fixation, which was used in 2.9% of cases, is reserved for the most complicated fractures with large soft-tissue defects or when immediate jaw bone repair is not possible 13. These surgical details and the distribution of procedures in this study indicate that our patient sample was in fact suffering from more complex fracture patterns, given that conservative treatment was so infrequently applied (Table 2).…”
Section: Discussionmentioning
confidence: 89%
“…12,13 Some studies have shown that the amount of internal fixation materials and fixation stability are closely related to increased infection risk. 14 Increased amount of fixation materials 15,16 and decreased stability 14 will increase the risk of infection. In recent years, use of the reconstruction plate has drawn much attention.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the prognosis of comminuted fracture treatment is related to the degree of commutation, use of internal fixation materials, and the movement of fractured bones in relation to infection. 14 Thus, unstable small fragments should be removed and larger fractures should be fixed as often as possible using a full loadbearing system. 17,18 Especially for patients with reinfection, it is best to use a reconstruction plate or a locking plate for fixation.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a paradigm shift in the past couple decades regarding the best secondary management of mandibles with nonunion and infection. 6 Traditionally, a two-stage approach of repair was advocated; the first stage involved controlling the infectious process with removal of involved teeth, drainage of any abscess, and the administration of antibiotics. After demonstration of resolution of the infection, then a secondary surgery could be undertaken with reduction and fixation of the bony segments.…”
Section: Nonunion and Infectionmentioning
confidence: 99%